The Present of Creativeness Development in Holding Structures Problems and Perspectives (Economic journal of Lesya Ukrainka Volyn National University, 2015)
Creativeness as an important resource of the holding development is investigated in this article. The dependence of creativeness from creative work and personal creative potential is analyzed; the content of creative act and its succession are shown; and parameters of creativeness are described too; the basic trends of creativeness activization in company are formed.Methodological aspects of creativeness analysis in holding structures and key factors of successful creative tasks decision, making the creation and acceptance of creative decisions are also investigated. It is shown that it is necessary individual but not collective approach while creativeness cultivation in the organization as two different types of people’s reaction concerning creative processes exist.Main descriptions of creative personalities and the part of their motivation in the creativeness development at the enterprise are examined. Trend of holding company managers’ work for the formation of creativism policy are founded.
Keywords: creativeness, creative work, creative potential, holding structures